2016
DOI: 10.1016/j.cub.2015.12.063
|View full text |Cite
|
Sign up to set email alerts
|

Interface Contractility between Differently Fated Cells Drives Cell Elimination and Cyst Formation

Abstract: SummaryAlthough cellular tumor-suppression mechanisms are widely studied, little is known about mechanisms that act at the level of tissues to suppress the occurrence of aberrant cells in epithelia. We find that ectopic expression of transcription factors that specify cell fates causes abnormal epithelial cysts in Drosophila imaginal discs. Cysts do not form cell autonomously but result from the juxtaposition of two cell populations with divergent fates. Juxtaposition of wild-type and aberrantly specified cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
188
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(200 citation statements)
references
References 48 publications
12
188
0
Order By: Relevance
“…We conclude by noting that recently there have been several interesting attempts at extending the Vertex Model description to three dimensions [85,[107][108][109][110][111][112]. While in principle possible, extending the AVM to a curved surface or making it fully three-dimensional would be quite involved.…”
Section: Discussionmentioning
confidence: 97%
“…We conclude by noting that recently there have been several interesting attempts at extending the Vertex Model description to three dimensions [85,[107][108][109][110][111][112]. While in principle possible, extending the AVM to a curved surface or making it fully three-dimensional would be quite involved.…”
Section: Discussionmentioning
confidence: 97%
“…Instead, the latter is a function of the relative cortical expansion and its relative thickness (compared with the brain size). Moreover, we showed that the folding of simulated growing cell monolayers can occur without the presence of different types of cells as in Tamulonis et al (2011), Bielmeier et al (2016, or differential tension between the boundary (apical and basal) edges of the cells, as in Š torgel et al (2016), Höhn and Hallmann (2011). In our simulations, all the cells were identical and only characterised by their normalised overall contractility, adhesion to their neighbours and proliferation rate.…”
Section: Resultsmentioning
confidence: 76%
“…Tissue folding is a frequently observed phenomenon, from blastula gastrulation (Tamulonis et al 2011;Rauzi et al 2013;Polyakov et al 2014), to the formation of brain convolutions (Tallinen et al 2014(Tallinen et al , 2016, gut villis Shyer et al 2013), cyst (Bielmeier et al 2016) and even crocodile head scales (Milinkovitch et al 2013). However, the causes of tissue buckling and folding are not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations